Editor's Corner: Green Materials - The Advancements and Applications of Natural Fibers - Edi Syafri; Vinod Ayyappan; Vijay Raghunathan; Sanjay Mavinkere Rangappa; Suchart Siengchin (Green Engineering Society, 2023)
After the industrial revolution, our world started shifting its focus towards sustainability and eco-friendly green materials to replace their synthetic counterparts. Cellulose fibers have played a significant role in human history, providing clothing and various products for many centuries. However, as technology advanced, the use of natural fibers became limited and minimized by synthetic materials. Growing environmental awareness has compelled industries to rethink their strategies, directing their attention toward sustainable and eco-friendly alternatives. In this context, natural cellulose fibers have gained a significant interest due to their eco-friendliness. These fibers can be derived from various sources, including trees, plants, and grasses. Cellulose fibers obtained from plants possess remarkable properties such as low density, wide availability, considerable mechanical strength, good thermal insulation, affordability, ease of processing, and non-toxicity